Nanostructure transition of young soot aggregates to mature soot aggregates in diluted diffusion flames. (15th April 2020) - Davis, Justin; Molnar, Eric; Novosselov, Igor
Abstract: In this study, the structural properties of soot produced in diffusion flames are analyzed to elucidate the formation of mature aggregates from large young particles. Soot samples are generated in a laminar diffusion inverted gravity flame reactor (IGFR) operated on methane, ethane, and ethylene with Ar dilution to reduce the flame temperature. Soot produced in temperature ranges from 1495K to 1568 K contains 100 nm–300nm particles with (i) isotropic or (ii) multiple core structures, supporting a soot maturation pathway where one young soot particle evolves into a mature fractal aggregate via an internal nucleation route. During the process, these large amorphous particles can form internal voids as the particle loses mass due to pyrolysis or oxidation. Transmission electron microscopy (TEM) shows that young soot aggregates contain a higher fraction of shorter fringes and highly curved aromatics (11% vs. 23%), which is in agreement with their higher organic carbon content (3.3%–5.4% vs. 12.1%–28.8% wt.). Increasing the flame temperature reduces the curvature of polycyclic aromatic hydrocarbons (PAHs) and allows for more efficient layer stacking as indicated by a higher percent of stacked fringes. For these gaseous fuels, carbonization appears to be primarily a function of the flame temperature and independent of the fuel composition. Graphical abstract: Image 1